COMMUNITY STRUCTURE OF CRABUca sp. IN MANGROVE FOREST AREAS SUNGAI CINGAM VILLAGE RUPAT ISLAND BENGKALIS REGENCY RIAU PROVINCE - Ilham Apriandi; Syafruddin Nasution; Afrizal Tanjung (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTUca sp. is one group of sea crab from Family: Ocypodidae which is spread in almost all Indonesian mangrove areas. This research was carried out in March 2018 located in Sungai Cingam VillageMangrove Forest, Rupat Island, Bengkalis Regency, Riau Province. This study aims to determine Uca sp. Crab community structure. Which includes Species, Density, Relative Density, Diversity, Uniformity, Dominance and Distribution Patterns. The method used in this study is a survey method and the determination of the sampling location by purposive sampling. Measurement of water quality parameters is carried out directly in place, namely temperature, salinity and pH. Substrate type dominately by sandy mud. Organic material classified as very high, ranges from 8.95 to 21.03% Water quality parameters are still supportive for Uca sp life. Crab type Uca sp. 5 species found were U rosea, U. forcipata, U. coartata, U.annulipes, U. perplexa. the highest density is found at station 3 that is far from human activity with a density value of 5.33 ind / m2. While the highest density of Uca sp. in every zone(highest tide boundary zone), is found in zone 1 with a value of 4.22 ind / m2.Keywords: Community structure, Uca sp.Mangrove, Rupat Island.